A lungfish survivor of the end-Devonian extinction and an Early Carboniferous dipnoan radiation. (2nd November 2019) - Challands, Tom J.; Smithson, Timothy R.; Clack, Jennifer A.; Bennett, Carys E.; Marshall, John E. A.; Wallace-Johnson, Sarah M.; Hill, Henrietta
Abstract : Until recently the immediate aftermath of the Hangenberg event of the Famennian Stage (Upper Devonian) was considered to have decimated sarcopterygian groups, including lungfish, with only two taxa, Occludus romeri and Sagenodus spp., being unequivocally recorded from rocks of Tournaisian age (Mississippian, Early Carboniferous). Recent discoveries of numerous morphologically diverse lungfish tooth plates from southern Scotland and northern England indicate that at least 10 dipnoan taxa existed during the earliest Carboniferous. Of these taxa, only two, Xylognathus and Ballgadus, preserve cranial and postcranial skeletal elements, which have yet to be described. Here we present a description of the skull of a new genus and species of lungfish, Limanichthys fraseri gen. et sp. nov., which hails from the very earliest Tournaisian in the Ballagan Formation of Burnmouth, southern Scotland. The new specimen represents the earliest definitive Tournaisian lungfish skull material, thus providing an invaluable insight into the response of this group – and, indeed, Sarcopterygii as a whole – immediately following the latest Devonian Hangenberg event. Phylogenetic analysis places Limanichthys fraseri within the Devonian 'phaneropleurid-fleurantiid' grade of lungfish and shows that the Carboniferous lungfish represent forms that have their origins deep in the Middle and Late Devonian as well as those from a unique Carboniferous radiation.http://zoobank.org/urn:lsid:zoobank.org:pub:101FFE43-42D5-4950-9169-A900113B6F1D